Plan de gestión estratégico para el manejo agronómico del cultivo de pitahaya (Hylocereus undatus) en Ecuador - Monserrate Ortega, Julio Nathael (2022)
Dragon fruit Hylocereus undatus are more difficult to grow, for this reason they are less frequent. This is a fruit very rich in vitamins and that has anti-inflammatory properties, many specialists recommend it in order to increase the body's defenses by improving the immune system, other of its many benefits are focused on its help in the formation of tissues, blood cells red, bones and collagen production. The pitahaya is a fruit that has long durability, it can be kept fresh for weeks and at room temperature, this is the main reason that motivates its cultivation and therefore it has been increasing over the years, it has become a potential source of economic income forming part not only of the national market but also of the international one. Based on all this, it is necessary to have a strategic management plan for the agronomic management of the pitahaya crop and thus ensure the quality and safety of the fruit.